Inhibition of kidney proximal tubular glucose reabsorption does not prevent against diabetic nephropathy in type 1 diabetic eNOS knockout mice. - Muralikrishna Gangadharan Komala; Simon Gross; Harshini Mudaliar; Chunling Huang; Katherine Pegg; Amanda Mather; Sylvie Shen; Carol A Pollock; Usha Panchapakesan (PLoS ONE, 2014)
BACKGROUND AND OBJECTIVE: Sodium glucose cotransporter 2 (SGLT2) is the main luminal glucose transporter in the kidney. SGLT2 inhibition results in glycosuria and improved glycaemic control. Drugs inhibiting this transporter have recently been approved for clinical use and have been suggested to have potential renoprotective benefits by limiting glycotoxicity in the proximal tubule. We aimed to determine the renoprotective benefits of empagliflozin, an SGLT2 inhibitor, independent of its glucose lowering effect. RESEARCH DESIGN AND METHODS: We induced diabetes using a low dose streptozotocin protocol in 7-8 week old endothelial nitric oxide (eNOS) synthase knockout mice. We measured fasting blood glucose on a monthly basis, terminal urinary albumin/creatinine ratio. Renal histology was assessed for inflammatory and fibrotic changes. Renal cortical mRNA transcription of inflammatory and profibrotic cytokines, glucose transporters and protein expression of SGLT2 and GLUT1 were determined. Outcomes were compared to diabetic animals receiving the angiotensin receptor blocker telmisartan (current best practice). RESULTS: Diabetic mice had high matched blood glucose levels. Empagliflozin did not attenuate diabetes-induced albuminuria, unlike telmisartan. Empagliflozin did not improve glomerulosclerosis, tubular atrophy, tubulointerstitial inflammation or fibrosis, while telmisartan attenuated these. Empagliflozin did not modify tubular toll-like receptor-2 expression in diabetic mice. Empagliflozin did not reduce the upregulation of macrophage chemoattractant protein-1 (MCP-1), transforming growth factor β1 and fibronectin mRNA observed in the diabetic animals, while telmisartan decreased transcription of MCP-1 and fibronectin. Empagliflozin increased GLUT1 mRNA expression and telmisartan increased SGLT2 mRNA expression in comparison to untreated diabetic mice. However no significant difference was found in protein expression of GLUT1 or SGLT2 among the different groups. CONCLUSION: Hence SGLT2 inhibition does not have renoprotective benefits independent of glucose lowering.